A novel wheat NAC transcription factor, TaNAC30, negatively regulates resistance of wheat to stripe rust. Issue 5 (14th April 2018) - Wang, Bing; Wei, Jinping; Song, Na; Wang, Ning; Zhao, Jing; Kang, Zhensheng
Abstract: NAC transcription factors are widespread in the plant kingdom and play essential roles in the transcriptional regulation of defense responses. In this study, we isolated a novel NAC transcription factor gene, TaNAC30, from a cDNA library constructed from wheat ( Triticum aestivum ) plants inoculated with the stripe rust pathogen Puccinia striiformis f. sp. tritici ( Pst ). TaNAC30 contains a typical NAM domain and localizes to the nucleus. Yeast one‐hybrid assays revealed that TaNAC30 exhibits transcriptional activity and that its C‐terminus is necessary for the activation of transcription. Expression of TaNAC30 increased when host plants were infected with a virulent race (CYR31) of the rust fungus Pst . Silencing of TaNAC30 by virus‐induced gene silencing inhibited colonization of the virulent Pst isolate CYR31. Moreover, detailed histological analyses showed that silencing of TaNAC30 enhanced resistance to Pst by inducing a significant increase in the accumulation of H2 O2 . Finally, we overexpressed TaNAC30 in fission yeast and determined that cell viability was severely reduced in TaNAC30 ‐transformed cells grown on medium containing H2 O2 . These results suggest that TaNAC30 negatively regulates plant resistance in a compatible wheat‐ Pst interaction. Abstract : TaNAC30 contains a typical NAM domain and localizes to the nucleus. Silencing of TaNAC30 enhanced resistance to the stripe rust pathogen Puccinia striiformis f. sp. tritici ( Pst ) by inducing a significant increase in the accumulation of H2 O2 . TaNAC30 negatively regulates plant resistance in a compatible wheat‐ Pst interaction.